BDB: biopanning data bank. Issue Volume 44:Issue D1(2016) (25th October 2015) - He, Bifang; Chai, Guoshi; Duan, Yaocong; Yan, Zhiqiang; Qiu, Liuyang; Zhang, Huixiong; Liu, Zechun; He, Qiang; Han, Ke; Ru, Beibei; Guo, Feng-Biao; Ding, Hui; et al.
Abstract: The BDB database (http://immunet.cn/bdb ) is an update of the MimoDB database, which was previously described in the 2012 Nucleic Acids Research Database issue. The rebranded name BDB is short for Biopanning Data Bank, which aims to be a portal for biopanning results of the combinatorial peptide library. Last updated in July 2015, BDB contains 2904 sets of biopanning data collected from 1322 peer-reviewed papers. It contains 25 786 peptide sequences, 1704 targets, 492 known templates, 447 peptide libraries and 310 crystal structures of target-template or target-peptide complexes. All data stored in BDB were revisited, and information on peptide affinity, measurement method and procedures was added for 2298 peptides from 411 sets of biopanning data from 246 published papers. In addition, a more professional and user-friendly web interface was implemented, a more detailed help system was designed, and a new on-the-fly data visualization tool and a series of tools for data analysis were integrated. With these new data and tools made available, we expect that the BDB database would become a major resource for scholars using phage display, with improved utility for biopanning and related scientific communities.